Post-Roman and medieval drying kilns : foundations of archaeological research - Rickett, Robert (Access archaeology., 2021)
Drying kilns, corn-dryers, and malting ovens are familiar features in post-Roman, Anglo-Saxon and medieval archaeology, yet few works of synthesis are available. Robert Rickett's pioneering dissertation is published here with additional material from Mark McKerracher which sets the work within the context of more recent studies.